I cannot figure this out...

## x/+2=x/3-3 ?

Tutors, please sign in to answer this question.

# 2 Answers

Hi Chris,

Assuming you meant:

x/(+2) = (x/3) - 3

or, a little prettier:

<pre>

x x

--- = --- - 3

+2 3

</pre>

(darn, doesn't look like wyzant will let us use html tags)

Then you can subtract x/3 from both sides:

x/2 - x/3 = x/3 -3 - x/3

x/2 - x/3 = -3

Then, get a common denominator:

(x/2)(3/3) - (x/3)(2/2) = -3

3x/6 - 2x/6 = -3

Next, combine like terms (fraction subtraction):

x/6 = -3

Now, multiply both sides by 6:

6(x/6) = (-3)6

x = -18

Hi Chris;

I am certain this is NOT...

x/(+2)=x/(3-3)

because 3-3=0. A numerator cannot be zero.

I think this is...

x/(+2)=(x/3)-3

+2 and 2 is the same thing.

So...

x/2=(x/3)-3

Let's eliminate fractions. 2 x 3 =6. Let's multiply both sides by 6...

6(x/2)=6[(x/3)-3]

3x=2x-18

Let's subtract 2x from both sides as we proceed to isolate x...

-2x+3x=2x-18-2x

x=-18

Let's check our work.

The original question was...

x/(+2)=(x/3)-3

-18/2=(-18/3)-3

-9=-6-3

-9=-9

If I misunderstood the original question, please let me know.

I hope this helps either way.